The Effect of Eco-Friendly Packaging on Consumer Purchase Intention: A Study of Beverage Sustainable Packaging Practices - Nur Fatin Nabilah Binti Azaini Imran; Nur Firyal Binti Noor Effendee; Nur Hazwani Husna Binti Mohd Faris; Nur Irdina Safi Binti Mohd Puad; Nitin Nitin; Vanshika Verma; Kumar Mayur; Hui Ling Lim; Wei Chien Ng; Meenu Baliyan; Daisy Mui Hung Kee (Journal of The Community Development in Asia, 2024)
Being among the biggest beverage manufacturers in the world, Coca-Cola has recently embraced a variety of sustainability measures, such as water conservation, reduced packaging, and the use of renewable energy. However, the idea begs the issue of whether consumers have the intention to purchase Coca-Cola if the product adopts greener practices. This study examines the effect of ecologically friendly packaging on consumer purchase intention, use Coca-Cola as a case study. An online survey was employed to gather primary data from 100 Coca-Cola customers in order to better comprehend and support the research findings. This research investigated whether environmental concerns about awareness of brand and Coca-Cola sustainable packaging practice and awareness of eco- friendly influence will affect the purchase intention of consumers on Coca-Cola. This research provides fresh insights on consumers’ perception of eco-friendly packaging, and how this perception may encourage consumer purchasing decisions.